A Malaysian professional communication skills in English framework for English for occupational purposes courses - Ahmad Tajuddin, Azza Jauhar (2015)
Malaysian employers have considerable reservations when it comes to graduates’ employability skills, particularly their flawed English language competence. Given the challenges faced by higher education institutions in Malaysia to match employers’ requirements, there is a need to initiate holistic and comprehensive research on the curriculum practices of current English for Occupational Purposes (EOP) courses. This study sought to better comprehend employers’ perspectives, expectations and practices in dealing with the English language demands of the workplace environment. The requirements demanded by Malaysian employers will determine the key definition of professional communication skills for successful workplace functions.